2019
DOI: 10.1108/dta-03-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Feature intersection for agent-based customer churn prediction

Abstract: Purpose Telecommunication has a decisive role in the development of technology in the current era. The number of mobile users with multiple SIM cards is increasing every second. Hence, telecommunication is a significant area in which big data technologies are needed. Competition among the telecommunication companies is high due to customer churn. Customer retention in telecom companies is one of the major problems. The paper aims to discuss this issue. Design/methodology/approach The authors recommend an Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In their proposed method, Pearson product-moment correlation coefficients were utilized in data preprocessing to extract effective features whereas, the k-NN technique (2≤k≤20) was employed to develop and evaluate many models to reduce effect of the noise on the classification Finally, the result showed that the K Nearest Neighbor (k-NN) algorithm performs well compared to the others with the accuracy for training is 80.45% and testing 97.78%. Moreover, in another study of Telecommunication Company,Sandhya et al, (2019) addressed the customer churn problem by recommending an Intersection-Randomized Algorithm (IRA) using Map Reduce functions to avoid data duplication in the mobile user call data. In addition, they also used the agent-based model (ABM) to predict the complex mobile user behaviour to prevent customer churn with a particular telecommunication service provider.…”
mentioning
confidence: 99%
“…In their proposed method, Pearson product-moment correlation coefficients were utilized in data preprocessing to extract effective features whereas, the k-NN technique (2≤k≤20) was employed to develop and evaluate many models to reduce effect of the noise on the classification Finally, the result showed that the K Nearest Neighbor (k-NN) algorithm performs well compared to the others with the accuracy for training is 80.45% and testing 97.78%. Moreover, in another study of Telecommunication Company,Sandhya et al, (2019) addressed the customer churn problem by recommending an Intersection-Randomized Algorithm (IRA) using Map Reduce functions to avoid data duplication in the mobile user call data. In addition, they also used the agent-based model (ABM) to predict the complex mobile user behaviour to prevent customer churn with a particular telecommunication service provider.…”
mentioning
confidence: 99%